Introduction to political theory - Graham, Paul; Hoffman, John (London ; New York, NY : Routledge, Taylor & Francis Group, 2022)
"This vibrant and significantly revised new edition is a comprehensive and accessible text for studying political theory in a changing world. Bringing together classic and contemporary political concepts and ideologies into one book, it introduces the major approaches to political issues that have shaped our world, and the ideas that form the currency of political debate. Consistently, it relates political ideas to political realities through effective use of examples and case studies making theory lively, contentious and relevant. With significant revisions which reflect the latest questions facing political theory in an increasingly international context, key features and updates include: Two brand new chapters on Migration, and Freedom of Speech and a significant new section on the radical right; Thought-provoking case studies to bring the theory to life including social media and internet regulation, Brexit and the EU, anti-vaxxer campaigns, surrogacy tourism, and autonomous anarchist zones; A revamped website, including podcasts, to aid study of, and reading around, the subject. Introduction to Political Theory, fourth edition is the perfect accompaniment to undergraduate study in political theory, political philosophy, concepts and ideologies, and more broadly to the social sciences and philosophy"--
"First edition published by Pearson Education Ltd. 2006. Third edition published by Routledge 2015" -- Title page verso.
Includes bibliographical references and index.
English
hbk
Description based on print version record and CIP data provided by publisher.
Keywords: Political science